Brain-derived neurotrophic factor Val66Met polymorphism modulates the effects of circadian desynchronization on activity and sleep in male mice - Phillips, Derrick J.; Blaine, Scott; Wallace, Naomi K.; Karatsoreos, Ilia N. (Frontiers in Neuroscience, 2023)
Introduction Understanding how environmental interact challenges with genetic predispositions modulate health and wellbeing is an important area of biomedical research. Circadian rhythms play an important role in coordinating the multitude of cellular and tissue processes that organisms use to predict and adapt to regular changes in the environment, and robust circadian rhythms contribute to optimal physiological and behavioral responses to challenge. However, artificial lighting and modern round-the-clock lifestyles can disrupt the circadian system, leading to desynchronization of clocks throughout the brain and body. When coupled with genetic predispositions, circadian desynchronization may compound negative outcomes. Polymorphisms in the brain-derived neurotrophic (BDNF) gene contribute to variations in neurobehavioral responses in humans, including impacts on sleep, with the common Val66Met polymorphism linked to several negative outcomes. Methods We explored how the Val66Met polymorphism modulates the response to environmental circadian desynchronization (ECD) in a mouse model. ECD was induced by housing adult male mice in a 20 h light-dark cycle (LD10:10; 10 h light, 10 h dark). Sleep and circadian activity were recorded in homozygous (Met) mice and their wild-type (Val) littermates in a standard 24 h LD cycle (LD12:12), then again after 20, 40, and 60 days of ECD. Results We found ECD significantly affected the sleep/wake timing in Val mice, however, Met mice maintained appropriate sleep timing after 20 days ECD, but not after 40 and 60 days of ECD. In addition, the rise in delta power at lights on was absent in Val mice but was maintained in Met mice. To elucidate the circadian and homeostatic contribution to disrupted sleep, mice were sleep deprived by gentle handling in LD12:12 and after 20 days in ECD. Following 6 h of sleep deprivation delta power was increased for both Val and Met mice in LD12:12 and ECD conditions. However, the time constant was significantly longer in the Val mice during ECD compared to LD12:12, suggesting a functioning but altered sleep homeostat. Discussion These data suggest the Val66Met mutation is associated with an ability to resist the effects of LD10:10, which may result in carriers suffering fewer negative impacts of ECD.